Analisis Kesulitan Membaca Permulaan Siswa dalam Pembelajaran Daring Kelas 3 SDN 01 Cikoko Jakarta Selatan - Ramadhani, Sulistyani Puteri; Ginting, Bobby Pranantha (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
This research was motivated by the difficulty of beginning reading in Bahasa Indonesia subject in online learning of the 3rd grade students at SDN 01 in Cikoko, South Jakarta. This research was conducted with the aim of overcoming students' beginning reading difficulties and looking for any factors that made students have difficulty reading and also describing the role of the teacher to be used as a solution in overcoming beginning reading difficulties. This research was conducted using qualitative research with descriptive methods using instrument values, observations, interviews, and document multiplication as data collection techniques. The research subjects were teachers and students of the third grade at SDN 01 Cikoko, South Jakarta. The results of this study are expected that students who have the difficulty on beginning reading can partake the teaching and learning activities in class well, have no difficulty when teaching and learning activities are carried out by online learning, the teacher can find solutions and what media are suitable to be used to overcome the difficulties of beginning reading experienced by some students of the third grade at SDN 01 Cikoko, South Jakarta.